Dreyfus and Haugeland on Heidegger and Authenticity - Henschen, Tobias (Human studies, 2012)
This paper tries to read some structure into the perplexing diversity of the literature on Heidegger’s concept of authenticity. It argues that many of the interpretations available rely on views that are false and cannot be Heidegger’s. It also shows that the only correct interpretation of Heidegger’s concept of authenticity emerges from a synthesis of Dreyfus’ later interpretation and Haugeland’s interpretation of this concept. A synthesis of these interpretations yields an interpretation, according to which Dasein’s being is authentic only if it is capable of using tools or language in radically new ways.